Benign hereditary chorea related to NKX2.1: expansion of the genotypic and phenotypic spectrum. (31st October 2013) - Peall, Kathryn J; Lumsden, Daniel; Kneen, Rachel; Madhu, Rajesh; Peake, Deirdre; Gibbon, Frances; Lewis, Hilary; Hedderly, Tammy; Meyer, Esther; Robb, Stephanie A; Lynch, Bryan; King, Mary D; et al.
Abstract : Aim: Benign hereditary chorea is a dominantly inherited, childhood‐onset hyperkinetic movement disorder characterized by non‐progressive chorea and variable degrees of thyroid and respiratory involvement. Loss‐of‐function mutations in NKX2.1, a gene vital to the normal development and function of the brain, lungs, and thyroid, have been identified in a number of individuals. Method: Clinical data from individuals with benign hereditary chorea identified through paediatric neurology services were collected in a standardized format. The NKX2.1 gene was analysed by Sanger sequencing, multiplex ligation‐dependent probe amplification, and microarray analysis. Results: Six of our cohort were female and four male, median age at assessment was 8 years 6 months (range 1y 6mo–18y). We identified 10 probands with NKX2.1 mutations; nine of these mutations are novel (including two whole‐gene deletions) and one has been previously reported. Of the 10 individuals, eight presented with muscle hypotonia and four had evidence of hypothyroidism or respiratory involvement. Only three out of the 10 individuals had the full triad of 'brain–lung–thyroid syndrome' symptoms. Additional clinical characteristics occurring in individual participants included growth hormone deficiency, pes cavus, kyphosis, duplex kidney, and obsessive–compulsive disorder. Interpretation: Our data suggest that the neurological phenotype is prominent in this condition and that many patients with benign hereditary chorea do not have the classic triad of brain–lung–thyroid syndrome. The extended phenotype may include obsessive–compulsive disorder and skeletal abnormalities. What this paper adds: This paper provides clinical and genetic characterization of a large BHC cohort. Nine novel NKX2.1 mutations are described. The clinical phenotype is expanded to include skeletal and psychiatric disorders. Details of the use and efficacy of medical therapies tried in these cases are given. This article is commented on by Rice on pages of this issue.